O contexto das políticas públicas para infância no campo - Renata Mendes Velloso (2008)
The present study is an analysis of the municipalization of Primary Education in the countryside. It was developed in five towns from Vale do Jequitinhonha, Minas Gerais: Berilo, Chapada do Norte, Francisco Badaró, Minas Novas and Virgem da Lapa. The object of the study was to comprehend and register the political mobilization process that happen in that region, which intend to guarantee the education from zero to six years-old children. The methodology of study involved three procedures: an analysis of documents such as the Primary Educational Legislation and documents related to the Program of Formation in Service for Primary Tutors PFSEI (short in Portuguese), done by the Christian Fund for Children FCC (short in Portuguese), including the pedagogic counselors, social assistants and children tutors from the community association in accordance to the referred institution; followed by interviews with leaderships which direct or indirectly undertook political actions with the City Halls in order to get financial resources for the Primary Education by the State, and finally, the attendance of part of the process through direct observation of the researcher from 2004 to 2006. The program is a result of the this study, delineated from the year of 2004 by a gradual democratic conquest of the transference of children taking care supported by the Christian Fund for Children to the City Halls. It was observed that this process set up tension, breakage and new ways of interaction between the political society and the local community associations, throughout effective actions and conflicts of the social assistants and children tutors. It was seen a precarious assistance to the children in the countryside, helping to understand that the legislation itself doesnt guarantee the right to the education. Gramsci and Mainardes studies offered the theoretical elements needed for all discussions about the relation between the State and the civil society, based on pressures and tensions which mark/characterize the process in movement and the ones not continuous.